Quantitative CT detects progression in COPD patients with severe emphysema in a 3-month interval - Konietzke, Philip; Wielpütz, Mark Oliver; Wagner, Willi Linus; Wünnemann, Felix; Kauczor, Hans-Ulrich; Heußel, Claus Peter; Eichinger, Monika; Eberhardt, Ralf; Gompelmann, Daniela; Weinheimer, Oliver (European radiology, 2020)
Chronic obstructive pulmonary disease (COPD) is characterized by variable contributions of emphysema and airway disease on computed tomography (CT), and still little is known on their temporal evolution. We hypothesized that quantitative CT (QCT) is able to detect short-time changes in a cohort of patients with very severe COPD.